Molecular characterization of NDM-1-producing Pseudomonas aeruginosa isolates from hospitalized patients in Iran - Mojtaba Shahin; Ali Ahmadi (BMC, 2021)
Abstract Background The emergence of carbapenem-resistant Pseudomonas aeruginosa is one of the most important challenges in a healthcare setting. The aim of this study is double-locus sequence typing (DLST) typing of bla NDM-1 positive P. aeruginosa isolates. Methods Twenty-nine bla NDM-1 positive isolates were collected during three years of study from different cities in Iran. Modified hodge test (MHT), double-disk synergy test (DDST) and double-disk potentiation test (DDPT) was performed for detection of carbapenemase and metallo-beta-lactamase (MBL) producing bla NDM-1 positive P. aeruginosa isolates. The antibiotic resistance genes were considered by PCR method. Clonal relationship of bla NDM-1 positive was also characterized using DLST method. Results Antibiotic susceptibility pattern showed that all isolates were resistant to imipenem and ertapenem. DDST and DDPT revealed that 15/29 (51.8%) and 26 (89.7%) of bla NDM-1 positive isolates were MBL producing isolates, respectively. The presence of bla OXA-10, bla VIM-2 , bla IMP-1 and bla SPM genes were detected in 86.2%, 41.4%, 34.5% and 3.5% isolates, respectively. DLST typing results revealed the main cluster were DLST 25-11 with 13 infected or colonized patients. Conclusions The presence of bla NDM-1 gene with other MBLs encoding genes in P. aeruginosa is a potential challenge in the treatment of microorganism infections. DLST showed partial diversity among 29 bla NDM-1 positive isolates.